Concepções e práticas de professores de ciências da natureza sobre ensino híbrido no contexto de uma formação continuada, em escolas sergipanas - Alves, Leonardo de Jesus (2025)
The continuous training process is fundamental for teacher updating. Through it, teachers have the possibility to acquire new skills about the use and application of methodologies and active approaches associated with the use of Digital Information and Communication Technologies (TDICs). The adoption of active methodologies and approaches that stimulate debate on the importance of collaborative work, mediated learning, autonomy, problematization of reality and protagonism should be taken into account for changing paradigms in contemporary education. During and after the pandemic, training in Hybrid Teaching (HS) became a reality for teachers of Natural Sciences (NC), in Sergipe. However, there is still a research gap regarding the effective impacts in teaching practice during and after these trainings. This fact made emerge this research, which aims to: analyze the conceptions and practices of teachers of Natural Sciences Teaching on the Hybrid Teaching and the contributions of a continuing education, carried out by the Group of Interdisciplinary Studies and Researches in Active Methodologies (GEPIMA), from the Federal University of Sergipe, for strengthening teaching practice in public schools in Sergipe. The research was developed with CN teachers from public schools of Aracaju/ SE, in the context of a continuing education in HE and Inverted Classroom (SAI), offered by UFS. It is a qualitative research-action type. After the definition of the problem, preliminary research was started - bibliographic survey and application of diagnostic questionnaire. Subsequently, the development and implementation of an action plan took place through the construction of a proposal for continuing training on EH and SAI. At that time, the participant observation of the implementation stage of the plan was made. Subsequently, the intervention plan was evaluated by means of a semi-structured interview. The data obtained were analyzed in light of Laurence Bardin’s Content Analysis. The results revealed that, although teachers had an understanding of SH, it was often superficial or fragmented. Heterogeneity was observed in the adoption of active methodologies and digital resources. Continuing education proved to be fundamental for the theoretical deepening and practical immersion in HE models, promoting a change in teachers' conception of HE. The teachers perceived HE as an ally in the development of essential skills, despite the challenges in the transition from the traditional model to the hybrid. The research emphasized the need to invest in continuing theoretical and practical training, aligned with school reality and the availability of resources. This study may contribute to the development of public policies for continuing teacher education, highlighting the importance of immersive courses with close monitoring for effective learning and practical application.